Sistema y método para la interpretación de la imaginación motora de los movimientos de ponerse de pie y sentarse basado en interfaz cerebro computadora - Triana Guzmán, Nayid (Universidad Antonio Nariño, 2023)
Brain-computer interface (BCI) systems based on electroencephalography (EEG) and motor imagination (MI), have shown promising advances for the motor rehabilitation of lower extremities. However, in the state of the art there has been little explored about the MR of the lower limb, especially little is known about MR for standing and sitting. By Therefore, this paper presents an EEG-based ICC system for MI interpretation of these types of movements. The purpose of this system is to restore some mobility to people with disorders severe neuromuscular disorders that cannot exert the force required to move the physical interface (mouse, keyboard, joystick, microphone, or other peripherals) that use standing devices to perform transition from sitting to bipedal position